Information on ‘Tatars’ in Chinese Historical Chronicles: “Song Shi” and Works of Li Xinchuan - R. T. Ganiev; P. I. Butsyk; I. R. Khamzin (Научный диалог, 2025)
This article analyzes the ethnonym ‘Tatars’ within the context of Chinese historical sources from the Song dynasty, particularly focusing on the dynastic history “Song Shi” and the writings of Li Xinchuan. The authors explore the variety of character representations of this ethnonym in Song-era documents, reflecting the complexity and multifaceted perceptions of this ethnic group by Chinese chroniclers. It is established that ‘Tatars’ (塔塔) first appear in “Song Shi” as competitors to the Black Tatars, to which Genghis Khan belonged. The study reveals that the cultural Tatars residing near Mount Yinshan maintained contacts with China from the end of the Tang dynasty and the Five Dynasties period until 984, but these relations were severed following the uprising of Li Jiqian. Furthermore, it is shown that Li Xinchuan was the first to note the emergence of the ethnonym ‘Mongol-Tatars’ with the rise of Genghis Khan's empire. Thus, the article underscores the significance of Chinese sources for studying the history of the Tatars and their interactions with regional peoples, while Li Xinchuan’s works represent a valuable contribution to understanding the ethnic and political history of Central Asia during the Song era and the early Mongol Empire.